Effectiveness of Barkley\'s Parenting Skills Training Program on Social Adjustment and Academic Performance in Children with Learning Disabilities - Mohammad Hossein Dehghani; Salar Faramarzi; Khosro Ramezani (Iranian Journal of Educational Research)
Objective: The objective of this research was to examine the impact of Barkley's parenting training on the social adjustment and academic achievement of children diagnosed with specific learning disabilities. Methods: The employed research methodology was semi-experimental, encompassing a pre-test, post-test, and follow-up design that included both an experimental group and a control group. The statistical population consisted of all mothers of students exhibiting specific learning disabilities in the city of Abadeh. A sample of 30 mothers of students with special learning disorders was selected, with 15 mothers being randomly allocated to the experimental group (receiving Barkley's Parenting Skills Training Program) and 15 to the control group. The implementation of Barkley's Parenting Skills Training Program (PSTP) occurred over the course of 8 sessions, each lasting 90 minutes. The instruments for measurement comprised Bell's Adjustment Inventory and Pham and Taylor (1999) Academic Performance Scale. For data analysis, the statistical techniques employed included multivariate analysis of variance and repeated measures analysis of variance. Results: In terms of social adjustment, the effect size was calculated at 0.12, while for academic performance, it was 0.41, reflecting the differences in scores between the experimental and control groups attributable to PSTP, with these changes in the experimental group being both stable and statistically significant. Conclusions: The findings indicated that PSTP exerts a significant influence on the enhancement of social adjustment and academic performance in children with specific learning disorders.